«ТАРКИБАДАХШОН» ДОСТОНИ ВА УНИНГ «ГЎРЎҒЛИ» ЭПОСИ ЎЗБЕК ВЕРСИЯСИДА ТУТГАН ЎРНИ - Жўраев, М.; Очилов, Н. (SCIENCE and SOCIETY, 2020)
The article is devoted to the analysis of the plot structure and ideological and artistic features of the dastan “Tarkibadakhshan”, recorded in the epic repertoire of the famous representative of the Sherabad dastan school, People’s Bakhshi of the Republic of Uzbekistan Chori Umirov. The artistic and aesthetic functions of the main motives are analyzed and a peculiar interpretation of epic images is determined.